Alive and at home: Five-year outcomes in older adults following emergency general surgery. Issue 2 (February 2021) - Guttman, Matthew P.; Tillmann, Bourke W.; Nathens, Avery B.; Saskin, Refik; Bronskill, Susan E.; Huang, Anjie; Haas, Barbara
Abstract : BACKGROUND: While the short-term risks of emergency general surgery (EGS) admission among older adults have been studied, little is known about long-term functional outcomes in this population. Our objective was to evaluate the relationship between EGS admission and the probability of an older adult being alive and residing in their own home 5 years later. We also examined the extent to which specific EGS diagnoses, need for surgery, and frailty modified this relationship. METHODS: We performed a population-based, retrospective cohort study of community-dwelling older adults (age, ≥65 years) admitted to hospital for one of eight EGS diagnoses (appendicitis, cholecystitis, diverticulitis, strangulated hernia, bowel obstruction, peptic ulcer disease, intestinal ischemia, or perforated viscus) between 2006 and 2018 in Ontario, Canada. Cases were matched to controls from the general population. Time spent alive and at home (measured as time to nursing home admission or death) was compared between cases and controls using Kaplan-Meier analysis and Cox models. RESULTS: A total of 90, 245 older adults admitted with an EGS diagnosis were matched with controls. In the 5 years following an EGS admission, cases experienced significantly fewer months alive and at home compared with controls (mean time, 43 vs. 50 months; p < 0.001). Except for patients operated on for appendicitis and cholecystitis, all remaining patient subgroups experienced reduced time alive and at home compared with controls ( p < 0.001). Cases remained at elevated risk of nursing home admission or death compared with controls for the entirety of the 5-year follow-up (hazard ratio, 1.17–5.11). CONCLUSION: Older adults who required hospitalization for an EGS diagnosis were at higher risk for death or admission to a nursing home for at least 5 years following admission compared with controls. However, most patients (57%) remained alive and living in their own home at the end of this 5-year period. LEVEL OF EVIDENCE: Epidemiological, level III. Abstract : Supplemental digital content is available in the text.